Determining the Prevalence of Pain in Adult Patients Hospitalized in a University Hospital in Western Türkiye: An Observational Point Prevalence Study - Erkan Özduran; Volkan Hancı; Yüksel Erkin; Ali Avcı; Ali Emircan Ilgınlı; Burakcan Budakın; Deniz Metin Açıkgöz; Gökhan Gökmen; Mehmet Fatih Erfidan; Muhammed Can Feda Dinç; Rana Elif Aydoğdu; Soner Demircan; et al. (Hitit Medical Journal)

(untitled)
Objective: Pain, called the fifth vital sign, is also known as an indicator of quality of life. This study aimed to investigate the prevalence and associated factors of pain in adult patients hospitalized in a university hospital in western Türkiye.Material and method: After obtaining ethical committee approval, this cross-sectional study investigated the prevalence of pain and associated factors in hospitalized patients who met the inclusion criteria using a face-to-face survey method between May 1-31, 2022. Sociodemographic data surveys were administered to the participants in the study. The Numeric Rating Scale (NRS) and the Brief Pain Inventory (BPI) were used to assess pain intensity. Pain intensity is defined as mild [1-3], moderate [4-6], or severe [7-10].Results: The prevalence of pain was found to be 68.5% among the 762 people included in the study. The average NRS was found to be 6.33±2.24. Among the patients with pain, 60 (11.7%) had mild pain, 210 (41%) had moderate pain, and 242 (47.3%) had severe pain. A significant difference was found in between in the presence of pain according to gender (p=0.034). A moderate positive correlation was found between the worst pain intensity in the last 24 h and the least pain intensity in the last 24 h (r=0.401, p